Bayesian model updating of stochastic dynamic soil-structure interaction systems with multiple resolutions - Bansal, Sahil (2014)
In this paper, the problem of stochastic modeling of dynamic soil-structure interaction systems and the corresponding model updating problem are considered. Ambient vibration or seismic vibration data can be used to update the model properties of dynamic soil-structure interaction systems. Most existing works for model updating of these types of systems consider only one choice of resolution without paying much attention to the effect of model resolution. In this paper, a Bayesian model updating methodology based on stochastic model classes with multiple resolutions is proposed. The effect of model resolution on the result of the Bayesian model updating will be shown. The proposed methods are illustrated with an example involving a dynamic soil-building-structure system.